Prevalence of Occupational Diseases caused by vibration, 1975 to 2022: National baseline survey (Central Asian Journal of Medical Sciences, 2025)
Objective: Prolonged occupational vibration exposure can cause neurological, musculoskeletal, and connective tissue disorders. Establishing a national baseline in Mongolia is essential to determine the prevalence of vibration-related occupational diseases and to guide evidence-based policy interventions. To establish baseline evidence on the point prevalence and characteristics of vibration-related occupational diseases among individuals diagnosed with work-related disabilities in Mongolia. Methods: A descriptive desk review was conducted using data from 10,219 registered occupational disease cases between 1975 and 2022. Vibration-related cases (ICD codes: G54, G54.1, T75, T75.2, M21) were identified in two stages. A total of 952 cases were analyzed using STATA 12.0. Results: Of the 10,219 cases, 952 (9.3%) were vibration-related, including 895 (94.1%) whole-body vibration (WBV) and 57 (5.9%) hand-arm vibration (HAV) cases. The mean age at loss of work ability due to vibration-related disease was 43.38 ± 6.32 years, with an average exposure duration of 17.62 ± 5.63 years. The mining sector showed the highest prevalence, at 224.86 cases per 100,000 working-age population. Among WBV-related diseases, nerve root and plexus disorders (G54) were most common (38.26 per 100,000), while acquired limb deformities (M21) predominated in HAV cases (1.98 per 100,000). Conclusion: Vibration-induced occupational diseases mainly affect the mining sector. The frequent neurological and musculoskeletal disorders highlight the need for accurate differential diagnosis to ensure effective prevention and management.